Expansion of Functional Myeloid-Derived Suppressor Cells in Controlled Human Malaria Infection - Lamsfus Calle, Carlos; Fendel, Rolf; Singh, Anurag; Richie, Thomas L.; Hoffman, Stephen L.; Kremsner, Peter G.; Mordmüller, Benjamin (Frontiers in Immunology, 2021)
Malaria can cause life-threatening complications which are often associated with inflammatory reactions. More subtle, but also contributing to the burden of disease are chronic, often subclinical infections, which result in conditions like anemia and immunologic hyporesponsiveness. Although very frequent, such infections are difficult to study in endemic regions because of interaction with concurrent infections and immune responses. In particular, knowledge about mechanisms of malaria-induced immunosuppression is scarce. We measured circulating immune cells by cytometry in healthy, malaria-naïve, adult volunteers undergoing controlled human malaria infection (CHMI) with a focus on potentially immunosuppressive cells. Infectious Plasmodium falciparum (Pf) sporozoites (SPZ) (PfSPZ Challenge) were inoculated during two independent studies to assess malaria vaccine efficacy. Volunteers were followed daily until parasites were detected in the circulation by RT-qPCR. This allowed us to analyze immune responses during pre-patency and at very low parasite densities in malaria-naïve healthy adults. We observed a consistent increase in circulating polymorphonuclear myeloid-derived suppressor cells (PMN-MDSC) in volunteers who developed P. falciparum blood stage parasitemia. The increase was independent of preceding vaccination with a pre-erythrocytic malaria vaccine. PMN-MDSC were functional, they suppressed CD4+ and CD8+ T cell proliferation as shown by ex-vivo co-cultivation with stimulated T cells. PMN-MDSC reduced T cell proliferation upon stimulation by about 50%. Interestingly, high circulating PMN-MDSC numbers were associated with lymphocytopenia. The number of circulating regulatory T cells (Treg) and monocytic MDSC (M-MDSC) showed no significant parasitemia-dependent variation. These results highlight PMN-MDSC in the peripheral circulation as an early indicator of infection during malaria. They suppress CD4+ and CD8+ T cell proliferation in vitro. Their contribution to immunosuppression in vivo in subclinical and uncomplicated malaria will be the subject of further research. Pre-emptive antimalarial pre-treatment of vaccinees to reverse malaria-associated PMN-MDSC immunosuppression could improve vaccine response in exposed individuals.